SUPERIOR INFERIOR CALYCES AXIS IN SAGITTAL VERSUS CORONAL PROJECTION OF NON CONTRAST ABDOMINAL MULTISLICE COMPUTED TOMOGRAPHY: AN ANATOMICAL STUDY IN SUPINE PCNL - Krisna, Muhammad Sidharta; Soeroharjo, Indrawarman; Ali, Zulfikar (Indonesian Urological Association, 2020)
Objective: Getting the right access to the kidney calyces that has been determined is the most important part of PCNL. Less optimal access can cause an increase in operating time and a decrease in stone free rate. The use of inferior calyx as access decreases the risk of complications, but there are difficulties in reaching the superior calyx, which affects the stone free rate. The angle and depth of the puncture on PCNL can be determined by coronal and sagittal cuts in the non contrast MSCT scan of the abdomen. Material & Methods: This is an analytical study with a prospective cross-sectional method. An analysis was done to 198 samples of patients in Kardinah Tegal Hospital. Samples were taken with 16 slices non-contrast abdominal MSCT using Philips MSCT MX16 (120 kVp; 2x0.75 mm slice thickness). Samples were collected with consecutive sampling method, excluding patients who had a history of other illnesses or surgical history that resulted in anatomical changes in kidney position, age<18 year old, BMI>30 (obesity), grade 4 hydronephrosis (calyces had disappeared). Reconstruction of 3D non contrast abdominal MSCT was performed by measuring the angle of the coronal cut which was simulated as a puncture in the supination position and sagittal cut which was simulated as puncture in pronation position. An imaginary line was drawn from the imaginary point between the iliac crest and 12th rib as high as 3th to 4th lumbar to the inferior renal calyx. Axis was drawn from the inferior renal calyx towards the superior renal calyx. Results: There is significant difference (P=0.000) in the angle of the imaginary line drawn from the inferior calyx to the superior calyx between the right supination position compared to the right pronation position. The angle in the supination position is more gentle 142.8 (±9.7)/(118-165) degrees compared to 96.5 (±13.2)/(11-138) degrees. On the left side, the angle formed from inferior calyx to the superior calyx in the supination position is more gentle 143.4 (±9.6)/(119-162) degrees) compared with 97.3 (±11.2)/(76-132) degrees formed in pronation position, with a value of P=0.000. Conclusion: PCNL puncture with an inferior calyx approach to reach the superior calix on abdominal MSCT without contrast will be easier to do in the supine position. This is because the angle from the inferior calyx to the superior calyx is more gentle in the supine position so that maneuvers are easier to do.